Examining Clinic-Based and Public Health Approaches to Ascertainment of HIV Care Status. (1st May 2015) - Christopoulos, Katerina A.; Scheer, Susan; Steward, Wayne T.; Barnes, Revery; Hartogensis, Wendy; Charlebois, Edwin D.; Morin, Stephen F.; Truong, Hong-Ha M.; Geng, Elvin H.
Abstract : Introduction: Clinic-based tracing efforts and public health surveillance data can provide different information about HIV care status for the same patients. The relative yield and how best to use these sources to identify and reengage out-of-care patients is unknown. Methods: At a large public HIV clinic in San Francisco, we selected a 10% random sample of active patients who were at least 210 days "late" for an HIV primary care visit as of April 1, 2013, for clinic-based outreach. Patients were considered out of care if they did not have an HIV primary care visit in the 210 days before April 1, 2013. We then matched the sample with the San Francisco Department of Public Health HIV surveillance registry. Patients with a CD4 or viral load result in the 210-day period were classified as in care. We compared results from both sources and estimated the cumulative incidence of disengagement from care for the full cohort of clinic patients. Results: Of 940 patients lost to follow-up, 95 were sampled. Clinic tracing found 60 (63%) in care, 23 (24%) not located, 9 (10%) out of care, 2 (2%) incarcerated, and 1 (1%) had died. Of 42 individuals surveillance classified as out of care, tracing found 22 (52%) were in care. Of 52 patients found to be in care by surveillance, 12 (23%) were out of care by clinic tracing or unable to be located. The naive estimate of the cumulative incidence of disengagement from care at 3 years for the active clinic cohort was 41.1% [95% confidence interval (CI): 37.6 to 44.5]. The use of surveillance data reduced this estimate to 12.7% (95% CI: 18.2 to 25.4), and when further corrected using tracing outcomes, the estimate dropped to only 6.4% (95% CI: 3.4 to 9.4). Conclusions: Clinic-based tracing and surveillance data together provide a better understanding of care status than either method alone. Using surveillance data to inform clinic-based outreach efforts may be an effective strategy, although tracing efforts are most likely to be successful if conducted in real time.